INTEGRASI MEDIA AUDIO, VIDEO, DAN VISUAL DALAM PENDIDIKAN AGAMA ISLAM DI ERA DIGITAL - Normaita Normaita; Nur Ellysa; Muhammad Haikal Ramadhan; Ahmad Bukhari; Abdul Azis; Muhammad Ramdani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT This article discusses the integration of audio, video, and visual media in Islamic Religious Education (IRE) learning in the digital era as a response to changes in students’ learning styles and advances in information technology. The purpose of this study is to analyze the roles, forms of implementation, and contributions of digital media integration in improving the effectiveness of Islamic Religious Education learning and fostering students’ religious character. This study employs a library research method by reviewing relevant scholarly sources, including books, accredited journal articles, and previous studies on digital learning media in Islamic education. The findings indicate that the integration of audio, visual, and audiovisual media enhances the quality of Islamic Religious Education learning through more concrete, interactive, and learner-centered content delivery that aligns with the characteristics of students in the digital age. Visual media help clarify abstract religious concepts, audio media support activities such as Qur’anic recitation, memorization, prayers, and tajwid pronunciation, while audiovisual media enrich learning experiences through educational videos, animations, worship simulations, and instructional films. Furthermore, the utilization of digital media can be strengthened through blended learning, flipped classroom approaches, learning management systems, interactive quizzes, and educational social media platforms. This study emphasizes that the successful integration of digital media depends not only on technological aspects but also on teachers’ role modeling, value reflection, digital literacy, and the cultivation of positive habits. Therefore, the integration of digital media in Islamic Religious Education contributes to improving learning effectiveness while supporting the development of students’ religious character, enabling them to become faithful, knowledgeable, morally upright, and responsible individuals in both real-life and digital environments. ABSTRAK Artikel ini mengulas penggabungan media audio, video, dan visual dalam pembelajaran Pendidikan Agama Islam (PAI) di era digital sebagai respons terhadap perubahan gaya belajar peserta didik dan perkembangan teknologi informasi. Tujuan kajian ini adalah menganalisis peran, bentuk implementasi, serta kontribusi integrasi media digital dalam meningkatkan efektivitas pembelajaran PAI dan pembentukan karakter religius siswa. Penelitian menggunakan metode studi pustaka (library research) dengan menelaah berbagai sumber ilmiah yang relevan, meliputi buku, artikel jurnal terakreditasi, dan hasil penelitian terdahulu yang membahas media pembelajaran digital dalam pendidikan Islam. Hasil kajian menunjukkan bahwa integrasi media audio, visual, dan audiovisual mampu meningkatkan kualitas pembelajaran PAI melalui penyajian materi yang lebih konkret, interaktif, dan sesuai dengan karakteristik peserta didik di era digital. Media visual membantu memperjelas konsep-konsep keagamaan yang abstrak, media audio mendukung pembelajaran tilawah, hafalan, doa, dan tajwid, sedangkan media audiovisual memperkaya pengalaman belajar melalui video, animasi, simulasi ibadah, dan film edukatif. Selain itu, pemanfaatan media digital dapat diperkuat melalui pendekatan blended learning, flipped classroom, sistem manajemen pembelajaran, kuis interaktif, dan media sosial edukatif. Kajian ini menegaskan bahwa keberhasilan integrasi media digital tidak hanya ditentukan oleh aspek teknologi, tetapi juga oleh keteladanan guru, penguatan refleksi nilai, literasi digital, dan pembiasaan perilaku positif. Dengan demikian, integrasi media digital dalam pembelajaran PAI berkontribusi terhadap peningkatan efektivitas pembelajaran sekaligus mendukung pembentukan karakter religius siswa yang beriman, berpengetahuan, berakhlak mulia, dan bertanggung jawab dalam kehidupan nyata maupun ruang digital.